The 5 love languages: the secret to love that lasts - Chapman, Gary. (Chicago: Northfield, 2015)
Between busy schedules and long days, expressing love can fall by the wayside. We forget to compliment, to give gifts "just because," to linger in our embrace. The things that say "I love you" seem to either not get said or not get through. This is a book about saying it-and hearing it-clearly. No gimmicks. No psychoanalyzing/ Just learning to express love in your spouse's language.
Keywords: Marriage. -- Communication in marriage. -- Love